2019
DOI: 10.1021/acs.joc.9b00105
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamate Esters Guide C(3)-Selective Xanthylation of Alkanes

Abstract: Owing to the pervasiveness of hydroxyl groups in natural isolates, alcohol derivatives are alluring directing groups. Herein, an alcohol-derived sulfamate ester guides the light initiated xanthylation of primary, secondary, or tertiary centers. This process enables formal directed deuteration, azidation, thiolation, and vinylation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…103 °C) which favors a seven-membered-ring transition state over the usual six-membered-ring. 241 , 242 …”
Section: N -Centered Radical Generation From N–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…103 °C) which favors a seven-membered-ring transition state over the usual six-membered-ring. 241 , 242 …”
Section: N -Centered Radical Generation From N–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…Cognizant of the emergence of sulfamyl radical‐directed halogen‐ [167, 168] and group‐transfer reactions, [169–171] Roizen and co‐workers, [172] Duan and co‐workers, [173] and Shu et al [174] have demonstrated that sulfamate esters [175] can serve as direct precursors to radicals under photochemical conditions (Scheme 45). The accessed sulfamyl radicals guide Giese reactions based on remarkable 1,6‐HAT processes, which proceed with site‐selectivity that has been historically inaccessible.…”
Section: Nitrogen‐centered Radicals Enable Hydrogen‐atom‐transfer Processes To Generate Remote Carbon‐centered Radicalsmentioning
confidence: 99%
“…[166] As ademonstration of synthetic value,subsequent hydrolysis of the imine to the ketone provides technology for obtaining g-C(sp 3 )-H functionalized ketones.A lternatively,t he versatile imine functionality can be retained through at wo-step, one-pot protection with benzoyl chloride. Cognizant of the emergence of sulfamyl radical-directed halogen- [167,168] and group-transfer reactions, [169][170][171] Roizen and co-workers, [172] Duan and co-workers, [173] and Shu et al [174] have demonstrated that sulfamate esters [175] can serve as direct precursors to radicals under photochemical conditions (Scheme 45). Thea ccessed sulfamyl radicals guide Giese reactions based on remarkable 1,6-HATp rocesses,w hich proceed with site-selectivity that has been historically inaccessible.…”
Section: Iminyl Radicals Direct Giese Reactionsmentioning
confidence: 99%
“…[166] As ademonstration of synthetic value,subsequent hydrolysis of the imine to the ketone provides technology for obtaining g-C(sp 3 )-H functionalized ketones.A lternatively,t he versatile imine functionality can be retained through at wo-step, one-pot protection with benzoyl chloride. Cognizant of the emergence of sulfamyl radical-directed halogen- [167,168] and group-transfer reactions, [169][170][171] Roizen and co-workers, [172] Duan and co-workers, [173] and Shu et al [174] have demonstrated that sulfamate esters [175] can serve as direct precursors to radicals under photochemical conditions (Scheme 45). Thea ccessed sulfamyl radicals guide Giese reactions based on remarkable 1,6-HATp rocesses,w hich proceed with site-selectivity that has been historically inaccessible.…”
Section: Iminyl Radicals Direct Giese Reactionsmentioning
confidence: 99%